2009
DOI: 10.1590/s0036-36342009000200006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neisseria meningitidis carriers in children under five years of age and teenagers in certain populations of Mexico City

Abstract: Prevalence of Neisseria meningitidis carriers in children under five years of age and teenagers in certain populations of Mexico City.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
13
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 22 publications
6
13
2
Order By: Relevance
“…We estimated the nasopharyngeal N. meningitidis carriage to be 2.7%, which appear lower than the generally quoted overall rate of 10% [70], and the average 3.5–35% reported in studies conducted in Africa [71], but at least consistent with that reported in Mexico (1.6%) [72]. The low carriage rates found in our study and those reported in Mexico are consistent with the low disease incidence rate reported in these two countries.…”
Section: Resultssupporting
confidence: 51%
“…We estimated the nasopharyngeal N. meningitidis carriage to be 2.7%, which appear lower than the generally quoted overall rate of 10% [70], and the average 3.5–35% reported in studies conducted in Africa [71], but at least consistent with that reported in Mexico (1.6%) [72]. The low carriage rates found in our study and those reported in Mexico are consistent with the low disease incidence rate reported in these two countries.…”
Section: Resultssupporting
confidence: 51%
“…1). Of these, 14 met the inclusion criteria and were included in the review, including seven studies from Brazil [33][34][35][36][37][38][39], three from Chile [40][41][42], and one each from Colombia [43], Cuba [32], Mexico [44], and Paraguay [45] (Fig. 2; Table 2).…”
Section: Literature Search Findings On Carriage In the Americasmentioning
confidence: 99%
“…One publication assessed carriage in Mexico. Espinosa de los Monteros and colleagues reported the epidemiology of N. meningitidis carriage isolates in children younger than 5 years and adolescents in Mexico City from September 2004 to April 2005 [44]. Using a nonprobabilistic group sampling method from the healthy population, investigators studied children attending daycare centers (n = 736) and adolescents in social rehabilitation centers (n = 774) or attending universities (n = 800); 2310 nasopharynx swabs were obtained from these individuals.…”
Section: Mexicomentioning
confidence: 99%
“…Of the published data identified, information relating to carriage is limited to children and adolescents from small populations residing within limited geographical areas [63, 64]. A carriage prevalence of 1·9% in children and 2·9% in adolescents was reported in Mexico [64], with Nm serogroups C and Y being the most frequently detected. Similarly, carriage of Nm was found to be 1·5% in a sample of schoolchildren in Venezuela [63].…”
Section: Introductionmentioning
confidence: 99%